2006
DOI: 10.1097/01.qai.0000221683.44940.62
|View full text |Cite
|
Sign up to set email alerts
|

Severe Liver Disease Associated With Prolonged Exposure to Antiretroviral Drugs

Abstract: CLD is an uncommon condition in HIV-positive individuals and might be associated with prolonged didanosine exposure. It may evolve causing severe liver complications, with variceal bleeding and portal thrombosis being particularly frequent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
2
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(132 citation statements)
references
References 47 publications
5
123
2
2
Order By: Relevance
“…More recently, some cases of non-cirrhotic portal hypertension have been described in HIV-infected patients (26)(27)(28)(29). In such cases, liver biopsy usually showed vascular lesions presenting as nodular regenerative hyperplasia.…”
Section: Hbv/hcv Co-infectionmentioning
confidence: 99%
“…More recently, some cases of non-cirrhotic portal hypertension have been described in HIV-infected patients (26)(27)(28)(29). In such cases, liver biopsy usually showed vascular lesions presenting as nodular regenerative hyperplasia.…”
Section: Hbv/hcv Co-infectionmentioning
confidence: 99%
“…Available information points toward didanosine as the antiretroviral agent linked to cases of noncirrhotic portal hypertension, which should discourage use of this agent. 100,109 With the continued decrease in its use, this complication should fade away and disappear over time. A conclusion which may be drawn from these cases of nodular regenerative hyperplasia is the need to obtain image studies, and in selected cases, also liver biopsy for diagnosis when HIV-infected patients have persistent and unexplained liver enzyme elevation while on HAART.…”
Section: Prevention and Management Of Haart Liver Toxicitymentioning
confidence: 99%
“…Of more concern is the report by Spanish authors of nine cases of portal hypertension complicated by variceal bleeding, ascites, or hepatic encephalopathy without known underlying liver disease. 100,101 Five patients were thought likely to have fibrosis, either through liver biopsy or transient elastography. Of note, portal thrombosis occurred in six cases.…”
Section: Acute Eventsmentioning
confidence: 99%
“…NRH can be related to conditions in which hepatic blood flow is altered [9]. PVT is usually a result of an underlying vascular abnormality and has also been found to occur at greater rates in HIV-infected patients with liver disease than in the general population [4]. Schiano et al [29] reported a series of HIV-infected patients with hepatoportal sclerosis (HPS), which may be attributed to intrahepatic microthrombi.…”
Section: Discussionmentioning
confidence: 99%